Wnt signaling in the regulation of adult hippocampal neurogenesis - Varela-Nallar, Lorena; Inestrosa, Nibaldo C. (Frontiers in Cellular Neuroscience, 2013)
In the adult brain new neurons are continuously generated mainly in two regions, the subventricular zone of the lateral ventricles and the subgranular zone (SGZ) in the hippocampal dentate gyrus. In the SGZ, radial neural stem cells give rise to granule cells that integrate into the hippocampal circuitry and are relevant for the plasticity of the hippocampus. Loss of neurogenesis impairs learning and memory, suggesting that this process is important for adult hippocampal function. Adult neurogenesis is tightly regulated by multiple signaling pathways, including the canonical Wnt/beta-catenin pathway. This pathway plays important roles during the development of neuronal circuits and in the adult brain it modulates synaptic transmission and plasticity. Here, we review current knowledge on the regulation of adult hippocampal neurogenesis by the Wnt/beta-catenin signaling cascade and the potential mechanisms involved in this regulation. Also we discuss the evidence supporting that the canonical Wnt pathway is part of the signaling mechanisms involved in the regulation of neurogenesis in different physiological conditions. Finally, some unsolved questions regarding the Wnt-mediated regulation of neurogenesis are discussed.